IMPLEMENTATION OF QUANTUM IMAGE HALFTONING ALGORITHM - Oktorianti, Anastasia Monika; Mutiara, Achmad Benny; Refianti, Rina (Prosiding KOMMIT, 2014)
Developing new computing methods and signal processing algorithms byborrowing from the principle of quantum mechanics is a very interesting and newresearch topic. By utilizing quantum algorithm in the process of computing, it isexpected that this algorithm can solved the problems of image processing fasterthan using a classical algorithm. In this paper, a quantum digital imagehalftoning algorithm will be presented.The image would be processed usingbitmap image (.bmp) and the applications would be created using Matlab R2009a.Test phase of the applications is using an image, lena.bmp. This application willshow three new images as results of three halftoning methods: binary thresholdmethod, ordered dithering method, and method with quantum algorithm. Themethod with quantum algorithm shows better than two others methods.